Translation Analysis On "Laundry Guidelines" Of Samsung Wf 8692 Nfv - Maskuri Srilistyanto, Dony, Dr. Anam Sutopo, M.Hum (2016)
This research studies translation analysis on "laundry guidelines" of samsung WF 8692 NFV. The objective of the study are to identify method of translation found in manual book and describe the accuracy and readability found in Laundry Guidelines of Samsung WF 8692 NFV. The writer employ descriptive qualitative. The data of this study are information taken from Laundry Guidelines of Samsung WF 8692 NFV and informant. The source of data are document and informant. The method of data collection is documentation method. The collected data are analyzed by using Peter Newmark theories. The method of analyzed the data is comparative method. The results of the research show that: first, the translation method found in this study are word for word, literal, semantic, communicative and faithful. From 74 data there are 2 data or 2,7 % belong to word for word, 28 data or 37,8 % belong to literal, 19 data or 25,7 % belong to semantic, 13 data or 17,6 % belong to comunnicative and 12 data or 16,2 % belong to faithful. The dominant method is literal. Second, from 74 data there are 48 data or 64,9 % readable, then less readable translation are 14 data or 18,9% and the last is not readable translation there are 12 data or 16,2 %. Third, from 74 there are 45 data or 60,8 % accurate, then less accurate translation are 21 data or 28,4% and the last is not accurate translation are 8 data or 10,8 %.